Control Studies Puddle with Planning Channel Cut (Shortcut) on the Channel Irrigation Sengkaling Kiri District Lowokwaru, Malang City - Akbar, Bagus; Harisuseno, Donny; Sumiadi , Sumiadi (Asian Journal of Social and Humanities, 2025)
The drainage system in Malang City currently relies on the Sengkaling Kiri irrigation network to discharge urban drainage water. However, the existing channel capacity is insufficient to accommodate the increasing water flow during rainfall events due to channel narrowing and sedimentation. This limitation has resulted in frequent waterlogging and localized flooding, particularly around Jl. Soekarno Hatta, Jl. Ahmad Yani, and Jl. Lt. Gen. Sutoyo. This research aims to evaluate the performance of the current drainage system, identify the primary causes of flooding, and propose effective solutions to reduce inundation in these critical areas. The study employs a descriptive and analytical approach, combining field surveys, hydrological data collection, and hydraulic modeling to assess the channel’s capacity and identify critical points of overflow. The findings reveal that the current Sengkaling Kiri irrigation network has experienced significant sedimentation and reduced cross-sectional area, leading to a capacity deficit during peak discharge events. Proposed solutions include channel widening, sediment removal, and the construction of alternative drainage routes, such as diverting part of the flow directly from the Sengkaling Kiri network to the nearest Sungai Brantas. These interventions are expected to significantly reduce waterlogging and improve flood management in the affected areas. The implications of this study highlight the importance of regular maintenance, capacity upgrades, and the integration of urban drainage systems with natural waterways to ensure long-term flood resilience in rapidly developing urban areas.